2006
DOI: 10.1007/s11908-006-0005-9
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics and prebiotics for gastrointestinal infections

Abstract: There is growing interest in and knowledge about the potential health-promoting benefits of both probiotics and prebiotics. Multiple mechanisms of action for the beneficial effect of probiotics and prebiotics have been postulated, including prevention of pathogenic bacteria growth, production of antimicrobial agents, stimulation of mucosal barrier function, and altering immunoregulation. Clinical trials support the efficacy of probiotics in the treatment of acute infectious diarrhea, the prevention of antibiot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 58 publications
(32 reference statements)
0
11
0
Order By: Relevance
“…As treatment, probiotics have so far been used most for gastrointestinal disorders, especially antibiotic-associated diarrhea (52), but the possibility that they can alter extraintestinal immune function is suggested by the efficacy of feeding Lactobacillus rhamnosus in improving eczema in children (53), an effect that might be related to its induction of increased IFN-␥ production by PBMCs stimulated with phytohemagglutinin or Staphylococcus aureus enterotoxin B (54). Other studies using the same Lactobacillus species have shown that feeding it to children with gastrointestinal inflammation (55) or IgE-associated dermatitis and cow's milk allergy (56) improves the clinical condition and increases the production of IL-10 and IFN-␥ by PBMCs.…”
Section: Altering Gut Flora To Alter Immune Functionmentioning
confidence: 99%
“…As treatment, probiotics have so far been used most for gastrointestinal disorders, especially antibiotic-associated diarrhea (52), but the possibility that they can alter extraintestinal immune function is suggested by the efficacy of feeding Lactobacillus rhamnosus in improving eczema in children (53), an effect that might be related to its induction of increased IFN-␥ production by PBMCs stimulated with phytohemagglutinin or Staphylococcus aureus enterotoxin B (54). Other studies using the same Lactobacillus species have shown that feeding it to children with gastrointestinal inflammation (55) or IgE-associated dermatitis and cow's milk allergy (56) improves the clinical condition and increases the production of IL-10 and IFN-␥ by PBMCs.…”
Section: Altering Gut Flora To Alter Immune Functionmentioning
confidence: 99%
“…4 Myriad studies have indicated a relationship between intake of foods containing probiotics and various health benefits. [5][6][7][8][9][10][11][12] Unfortunately, these products may be underutilized due to a lack of public familiarity with probiotic products and low awareness of their benefits. It has been shown that following an education program, most participants show an interest in increasing intake of functional foods including yogurt.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple laboratory studies have shown beneficial effects of Lactobacillus strains against single pathogenic bacterial strains in in vitro and in vivo systems [7,8] . During the last few years, there has been an exponential increase of clinical trial reports and reviews in the literature pertaining to the utility of probiotics in gastrointestinal and allergic diseases [9][10][11][12][13][14][15][16][17][18][19][20][21] . Many small studies utilizing Lactobacillus and Bifidobacteria have shown beneficial effects such as better weight gain and improved www.wjgnet.com feeding tolerance [22] in neonates, and efficacy against neonatal necrotizing enterocolitis (NEC) [23][24][25] and sepsis [24] .…”
Section: Introductionmentioning
confidence: 99%